2023
DOI: 10.1097/01.nep.0000000000001085
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Strategies for Health Advocacy for Undergraduate Nursing Students: A Scoping Review

Abstract: AIM The goal of this study was to identify strategies for teaching health advocacy for undergraduate nursing students. BACKGROUND Although health advocacy is a core skill of professional nursing practice, there are challenges in the health advocacy approach in nursing education. METHOD The databases LILACS, IBECS, BDENF, Medline, Web of Science, CINAHL, and the Cochrane Library were searched, without limit of time and language, for this scoping review; 11 articles were included. Data were analyzed and synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Little is known about US nursing and midwifery students' instruction on health policy, their educational experiences around advocacy, or their political participatory behaviors and attitudes. 3,4,8,9 A 2022 literature review on policy advocacy curriculum in prelicensure nursing programs found inconsistent teaching strategies. A lack of evidence regarding the effectiveness of different pedagogical approaches was noted, with no consensus on essential topics in health policy curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Little is known about US nursing and midwifery students' instruction on health policy, their educational experiences around advocacy, or their political participatory behaviors and attitudes. 3,4,8,9 A 2022 literature review on policy advocacy curriculum in prelicensure nursing programs found inconsistent teaching strategies. A lack of evidence regarding the effectiveness of different pedagogical approaches was noted, with no consensus on essential topics in health policy curriculum.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 The importance of tailoring health policy curricula to the role of the nurse at each level of nursing education, weaving health policy content into other didactic courses, and engaging nursing faculty in health policy activities as role models was emphasized. 4,9,25 The AACN published a 2021 revised framework for nursing curriculum that incorporated recommendations to improve health policy instruction. 19 Interpreting, evaluating, and leading change in health policy, as well as advocating for professional autonomy, are presented as core concepts for nursing practice.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations